5-Aminolevulinic Acid and Contrast-Enhanced Ultrasound: The Combination of the Two Techniques to Optimize the Extent of Resection in Glioblastoma Surgery. (16th November 2020) - Pepa, Giuseppe Maria Della; Ius, Tamara; Rocca, Giuseppe La; Gaudino, Simona; Isola, Miriam; Pignotti, Fabrizio; Rapisarda, Alessandro; Mazzucchi, Edoardo; Giordano, Carolina; Dragonetti, Valentino; Chiesa, Silvia; Balducci, Mario; et al.
Graphical Abstract: